Kinetics of the alcoholic fermentation of cane molasses - Tuazon, Lourdes O.; Clemente, Amando (Quezon City Department of Chemistry, College of Liberal Arts, University of the Philippines Diliman, 1954)
This work was carried out to find out how the temperature, the pH, the nutrient concentration, and the yeast concentration affect the rate of the alcoholic fermentation of cane molasses by yeasts. The fermentation rate was measured by gravimetric method: weighing the carbon dioxide evolved, which was dried with anhydrous calcium chloride and absorbed with soda lime, at one hour intervals. By varying one factor while keeping the rest constant, the relationship between that factor and the rate was determined. Upon plotting the specific rate constants against the various factors, characteristic graphs were obtained which showed an optimum temperature of 40oC, an optimum pH of 4.33, an optimum (NH4)2SO4 concentration of 0.02 g / 8 g yeast / 16 g molasses in 100 ml solution, and an enormous increase of the rate with increase in yeast concentration. Marked discrepancies in the results could be explained by complexities in the yeast metabolic processes.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, March 1954.
Keywords: Kinetics; Fermentation; Molasses